Immediate and Late Effects of Pulse Widths and Cycles on Bipolar, Gated Radiofrequency-Induced Tissue Reactions in in vivo Rat Skin - Kim HK; Kim HJ; Kim JY; Ban MJ; Son J; Hwang Y; Cho SB (Dove Medical Press, 2023)
Hee Kyung Kim,1,* Hyun-Jo Kim,2,* Jae Yun Kim,3 Myung Jin Ban,4 Jiwon Son,5 Yongsung Hwang,5,6 Sung Bin Cho7 1Department of Pathology, Soonchunhyang University Bucheon Hospital, Bucheon, Korea; 2CNP Skin Clinic, Cheonan, Korea; 3Department of Dermatology, Soonchunhyang University Hospital, Cheonan, Korea; 4Department of Otorhinolaryngology-Head and Neck Surgery, Soonchunhyang University Hospital, Cheonan, Korea; 5Soonchunhyang Institute of Medi-Bio Science (SIMS), Soonchunhyang University, Cheonan, Korea; 6Department of Integrated Biomedical Science, Soonchunhyang University, Cheonan, Korea; 7Yonsei Seran Dermatology and Laser Clinic, Seoul, Korea*These authors contributed equally to this workCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, Geumcheon REMAIN CITY 6F, 224 Siheung-daero, Geumcheon-gu, Seoul, 08628, Korea, Tel +82 2-2135-1375, Fax +82 70-8250-1375, Email drsbcho@gmail.comBackground: Single to multiple pulse packs of bipolar, alternating current radiofrequency (RF) oscillations have been used for various medical purposes using invasive microneedle electrodes. This study was designed to evaluate the effects of pulse widths and cycles of RF pulse packs on immediate and delayed thermal tissue reactions in in vivo rat skin.Methods: RF energy at the frequency of 1 MHz and power of 70 W was delivered at each experimental setting into in vivo rat skin at 1.5-mm microneedle penetration, and then, tissue samples were obtained after 1 h and 3, 7, 14, and 21 days and histologically analyzed.Results: A single-pulse-pack RF treatment generated coagulative necrosis zones in the dermal peri-electrode area and zones of non-necrotic thermal reactions in the dermal inter-electrode area. Multiple pulse-pack, RF-treated rat skin specimens revealed that the number and size of peri-electrode coagulative necrosis were markedly decreased by increasing the number of pulse packs and accordingly decreasing the conduction time of each pulse pack. The microscopic changes in RF-induced non-necrotic thermal reaction in the inter-electrode area were more remarkable in specimens treated with RF of 7 or 10 pulse packs than in specimens treated with RF of 1- 4 pulse packs.Conclusion: The gated delivery of multiple RF pulse packs using a bipolar, alternating current, 1-MHz RF system using insulated microneedle electrodes efficiently generates non-necrotic thermal tissue reactions over the upper, mid, and deep dermis and subcutaneous fat in the inter-electrode areas.Keywords: radiofrequency, bipolar, alternating current, gated pulse, tissue reaction, rat